Towards a Total Synthesis of the Antibiotic Lysolipin I - Rudolf O. Duthaler; Christoph Heuberger; Urs H.-U. Wegmann; Veronica Scherrer (CHIMIA)
The original objective of total syntheses was the ultimate proof of structures of natural products. Since this is now much more efficiently done by X-ray analysis, the scientific significance of such work should be shifted to the preparative aspect, which is based on good strategies and progress of synthetic methodology. This report summarizes our efforts directed to a total synthesis of the heptacyclic antibiotic lysolipin I. The crucial point of our synthetic strategy is the use of a cyclohexanone as precursor for the phenolic ring F. In addition to several other advantages, this saturated ring allows a stepwise build-up of steric strain and controls the diastereoselectivity by virtue of additional asymmetric centers relating the configurations of isolated centers of chirality. The scope and limitations of the access to 2-aryl-cyclohexanone derivatives by Michael-addition to p-quinones has been evaluated on a broad basis. A regioselective monoprotection of substituted hydroquinones could be achieved by reductive phosphorylation of p-quinones with phosphites. In relation to a different approach, a new method for the preparation of nitroaromatic compounds by cyclocondensation has been devised.